Distance Learning as an Educational Trend in Higher Education - N. A. Seliverstova; M. G. Solnyshkina (Moscow Polytechnic University, 2021)
The case study research strategy describes variations in the educational and professional trajectories of part-time students in comparison with their attitude to distance learning, the goal of higher education, and their professional future of the individual. This research strategy makes it possible to present distance learning as a modern educational trend. It has been determined that in the system of continuing education, distance learning is (1) a tool for changing a profession, (2) part of a well-thought-out career strategy, (3) a guarantee of employment, (4) a way to legitimize a professional status, (5) a form that facilitates obtaining a diploma of higher education, (6) "future education", education for the future. The subjective meanings of distance education in connection with motivation, the purpose of training, the attitude of students to it are revealed. For students receiving higher education, this is "self-education," for those whose goal is a diploma, it is "formality", "superficial mastering of disciplines." The authors conclude that the consideration of correspondence education in the context of continuity allows us to identify trends in individualization, diversification (the diversity and variability of educational programs, creating opportunities for choice), informatization, and individualization. An assessment of the prospects for extramural higher education based on the experience of forced distance learning (March-June 2020) is given.